Ending Intimate Partner Violence after pregnancy: Findings from a community-based longitudinal study in Nicaragua - Valladares Eliette; Salazar Mariano; Öhman Ann; Högberg Ulf (BMC, 2009)
Abstract Background Although reducing intimate partner violence (IPV) is a pervasive public health problem, few longitudinal studies in developing countries have assessed ways to end such abuse. To this end, this paper aims to analyze individual, family, community and societal factors that facilitate reducing IPV. Methods A longitudinal population-based study was conducted in León, Nicaragua at a demographic surveillance site. Women (n = 478) who were pregnant between 2002 and 2003 were interviewed, and 398 were found at follow-up, 2007. Partner abuse was measured using the WHO Multi-country study on women's health and domestic violence questionnaire. Women's socio demographic variables, perceived emotional distress, partner control, social resources, women's norms and attitudes towards IPV and help-seeking behaviours were also assessed. Ending of abuse was defined as having experienced any abuse in a lifetime or during pregnancy but not at follow-up. Crude and adjusted odds ratios were applied. Results Of the women exposed to lifetime or pregnancy IPV, 59% reported that their abuse ended. This finding took place in a context of a substantial shift in women's normative attitudes towards not tolerating abuse. At the family level, no or diminishing partner control [ORadj 6.7 (95%CI 3.5-13)] was associated with ending of abuse. At the societal level, high or improved social resources [ORadj 2.0 (95%CI 1.1.-3.7)] were also associated with the end of abuse. Conclusion A considerable proportion of women reported end of violence. This might be related to a favourable change in women's norms and attitudes toward gender roles and violence and a more positive attitude towards interventions from people outside their family to end abuse. Maintaining and improving social resources and decreasing partner control and isolation are key interventions to ending abuse. Abuse inquiring may also play an important role in this process and must include health care provider's training and a referral system to be more effective. Interventions at the community level are crucial to reducing partner violence.